2017
DOI: 10.1002/prot.25343
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction between the strawberry allergen Fra a 1 and an associated partner FaAP: Interaction of Fra a 1 proteins and FaAP

Abstract: The strawberry fruit allergens Fra a 1.01E, Fra a 1.02 and Fra a 1.03 belong to the group of pathogenesis-related 10 (PR-10) proteins and are homologs of the major birch pollen Bet v 1 and apple allergen Mal d 1. Bet v 1 related proteins are the most extensively studied allergens but their physiological function in planta remains elusive. Since Mal d 1-Associated Protein has been previously identified as interaction partner of Mal d 1 we studied the binding of the orthologous Fra a 1-Associated Protein (FaAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
(148 reference statements)
3
10
0
Order By: Relevance
“…[61] Although the physiological significance is not clear, Fra a proteins were further shown to form a tight binding interaction with a small protein of unknown function termed Fra an associated protein (FaAP). [40] Two models of PR10/Bet v1-like protein involvement in flavonoid biosynthesis consistent with the aforementioned lines of evidence have been proposed ( Figure 4). The first suggests that PR10/Bet v1-like proteins might function as "chemical chaperones" which bind flavonoid intermediates and shuttle them within the cell.…”
Section: Flavonoidssupporting
confidence: 61%
See 3 more Smart Citations
“…[61] Although the physiological significance is not clear, Fra a proteins were further shown to form a tight binding interaction with a small protein of unknown function termed Fra an associated protein (FaAP). [40] Two models of PR10/Bet v1-like protein involvement in flavonoid biosynthesis consistent with the aforementioned lines of evidence have been proposed ( Figure 4). The first suggests that PR10/Bet v1-like proteins might function as "chemical chaperones" which bind flavonoid intermediates and shuttle them within the cell.…”
Section: Flavonoidssupporting
confidence: 61%
“…Shortly thereafter, isothermal titration calorimetry and crystallographic analyses confirmed that Fra a proteins differentially and selectively bind flavonoids but not early phenylpropanoid pathway intermediates (Section 3.5) [61] . Although the physiological significance is not clear, Fra a proteins were further shown to form a tight binding interaction with a small protein of unknown function termed Fra an associated protein (FaAP) [40] …”
Section: Roles In Plant‐specialized Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasmid construct pQE70 fra a 1.02 generated in a previous study [ 16 , 22 ] was used for transformation in the expression strain Escherichia coli ( E . coli ) BL21 (DE3) pLysS.…”
Section: Methodsmentioning
confidence: 99%